VALUE OF LOCAL WISDOM IN THE MYTH OF MERIAM TEGAK AND THE LEGEND OF PILANG ISLAND - Suhardi; Harry Andheska; Cut Purnama Sari (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
ABSTRACT The purpose of this research is to explore the values of local wisdom contained in the myth of Meriam Tegak and the legend Pilang Island. The research method used is qualitative descriptive. Data collection techniques are carried out using document techniques. Analysis of research data is carried out using content analysis techniques. The results obtained are the myth of the upright cannon and the legend of Pilang Island contains the value of local wisdom, such: (1) religious, (2) honesty, (3) not denouncing, (4) keeping the heart, (5) patient, (6) meek, (7) responsibility, and (8) the value of trust. The conclusion of the research is the myth of Meriam Tegak and the legend of Pilang Island contains religious values (Islam), ethical values, social, hard work, and educational values. The eight values of local wisdom combine to build a whole storyline of myths and legends. In addition, the eight values also decrypt local wisdom values. Keywords: values of local wisdom, myths, and legends